Neuropatologia da cinomose canina - Silva, Marcia Cristina da (2009)
Canine distemper is one of the most prevalent viral diseases of dogs. Several cases are diagnosed in a daily basis in private practices and veterinary hospitals around the country. Most cases of neurological manifestation of canine distemper are fatal and the diagnosis confirmation by histopathology is often necessary. Canine distemper encephalitis is the main cause of death or reason for euthanasia in dogs necropsied at the Laboratório de Patologia Veterinária (LPV) of the Universidade Federal de Santa Maria (UFSM). Consequently the large number of canine distemper cases in the LPV-UFSM files prompted the performance of a retrospective study consisting of 620 neurologic cases of canine distemper which served as the basis for a prospective study on the neuro-histopathologic aspects of the disease. The current study was carried out to perform a detailed histopathologic investigation on the changes in the central nervous system (CNS) of dogs affect by canine distemper aiming to help students of veterinary pathology and veterinary pathologists in the correct diagnose of this disease. Seventy dogs necropsied at the LPV-UFSM and with diagnosis of canine distemper confirmed by the finding of characteristic inclusion bodies in the CNS were included in the study. In order to determine the prevalence of the lesions, several anatomical regions were selected from the brain and spinal cord; these sites were consistently microscopically examined in each case. Overall, most affected anatomical regions were, in decreasing order of frequency: cerebellum (91.4%), diencephalon (78.6%), frontal lobe (75.7%), pons (72.9%) and mesencephalon (70.0%). Demyelination was the most prevalent lesion; it was observed in 91.4% of the cases and was located mainly in the cerebellum (88.6%), pons (65.7%) and diencephalon (61.4%). The five structures most affected by demyelination were: roof of the fourth ventricle (68.6%), cerebellar folia (61.4%), cerebellar medulla (61.4%), cervical spinal cord (46.3%) and mesencephalic tegment (40.0%). Other lesions and their prevalence were non-suppurative encephalitis (70.0%), non-suppurative leptomeningitis (44.3%), non-suppurative myelitis (35.2%), encephalomalacia (31.4%), nonsuppurative myelitis (18.5%), laminar cortical necrosis (17.1%), myelomalacia (13.0%), nonsuppurative ependymitis (7.1%) and plexochoroiditis (1.4%). The occurrence of the inclusion bodies in the cells of the CNS was: astrocytes (82.8%), neurons (44.3%), gemistocytes (31.4%), ependymal cells (22.8%), meningothelial cells (4.3%) and cells of the choroids plexus (1.4%).